If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(8x+5)=(4x+
We move all terms to the left:
(8x+5)-((4x+)=0
We add all the numbers together, and all the variables
(8x+5)-((+4x)=0
We get rid of parentheses
8x-((+4x)+5=0
| 2x+19=10x+-45 | | 2x+18=10x-45 | | (X+5)(3X-4)-6(x2+2)+4=0 | | 6(3w+10)/4=2 | | 5m+11=23+3m | | 4(x+3)=2(x-9) | | 5x=13=-27-3x | | (c+3)(c-5)=0 | | s=3+3/5 | | 2y-3=7y-38 | | 25+95+x=180 | | 30/24=100/x | | 120+38+x=180 | | 25730=x/100 | | 10+20+x=180 | | 18-7m=30 | | 3x2−20x−7=0 | | 105+30+x=180 | | 39+75+x=180 | | 25+110+x=180 | | 38+120+x=180 | | 2)4x+3)=10x-2 | | 2(2l+9)=34 | | 1x=32+3/2 | | 8x+1=12x-17 | | 8-9x=-12x-1 | | 3x+3=x8 | | -5(2x-6)=80 | | 2•(X+3)+2=x+8 | | y5=11 | | 4e-9=39 | | 2(x+3)+2=x-1 |